Cognitive-Behavioral Therapy for Postbariatric Surgery Patients With Mental Disorders: A Pilot Study - Rudolph, Almut; Hilbert, Anja (Frontiers in Psychiatry, 2020)
Background: Binge-eating disorder (BED) and major depressive disorder (MDD) following bariatric surgery are significant predictors for less post-operative weight loss and/or weight regain, however, cognitive-behavioral therapy (CBT) addressing these disorders following surgery has not been investigated so far. Objective: This study examined feasibility of a short-term CBT based on evidence-based manuals for BED and MDD adapted to patients following bariatric surgery, and its effectiveness in improving weight loss outcome, psychopathology, and psychosocial functioning. Materials and Methods: In an uncontrolled proof-of-concept study, the CBT manual was piloted in N = 7 patients who had undergone Roux-en-Y Gastric Bypass surgery at least six months before. Weight loss, eating disorder psychopathology, depressive symptoms, and self-esteem were assessed using clinical interviews and self-report questionnaires at pre-treatment, post-treatment, and 3-month follow-up. Results: A significant reduction of body weight and medium to large effects in the improvement of eating disorder psychopathology, depressive symptoms, and self-esteem from pre-treatment to post-treatment were found. Most of those changes remained stable during the 3-month follow-up period. Study retention was 71.4%. Conclusions: Feasibility and effectiveness of CBT for patients with BED or MDD following bariatric surgery were documented. Adaptations of the study procedure for the proof of efficacy in randomized-controlled studies are discussed.